ELEMENTS WITH THE USE OF A COMMUNICATIVE COMPONENT - Begmatov Mukhtor (Scholar Express Journal, 2023)
The article examines applied elements with a communicative component, reveals that they concretize, complement and implement events occurring in the basic structure of expression, and this is confirmed by examples from German literature. In addition, the article points out the repeatability and expansion of the properties inherent in applied elements, that applied elements differ sharply from other linguistic phenomena in their degree of prevalence, that applied elements can manifest various structural forms of the applied device.
Keywords: Application device; application element; communicative function; basic expression